2006
DOI: 10.1002/path.1938
|View full text |Cite
|
Sign up to set email alerts
|

Development of testicular inflammation in the rat involves activation of proteinase-activated receptor-2

Abstract: Mast cells are involved in early events crucial to inflammation and autoimmune disease. Recently, proteinase-activated receptor-2 (PAR(2)), a G-protein coupled receptor important to injury responses, was shown to be activated by mast cell tryptase. To investigate whether mast cells and PAR(2) are involved in the development and/or aggravation of testicular inflammation, we studied acute and chronic inflammatory models in the rat. In normal testes, PAR(2) was detected immunohistochemically in macrophages, in pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 49 publications
4
31
0
Order By: Relevance
“…In our study we also found that TNF-␣ induced the expression and the secretion of MCP-1 and IL-6, which are considered prototype inflammatory markers and are involved in the attraction of immune cells to sites of inflammation (48,49). Production of cytokines, in general, and MCP-1 and IL-6 in particular, is in line with reports of rodent peritubular cells, which are known to secrete a number of cytokines (9).…”
Section: Discussionsupporting
confidence: 89%
“…In our study we also found that TNF-␣ induced the expression and the secretion of MCP-1 and IL-6, which are considered prototype inflammatory markers and are involved in the attraction of immune cells to sites of inflammation (48,49). Production of cytokines, in general, and MCP-1 and IL-6 in particular, is in line with reports of rodent peritubular cells, which are known to secrete a number of cytokines (9).…”
Section: Discussionsupporting
confidence: 89%
“…Mast cells involve in the granuloma formation in the testis through proteinase-activated receptor-2 (PAR2) activation. PAR2 is localized to the MPCs, macrophages, and acrosomes of spermatids in rat testis, and involved in the development of testicular inflammation (Iosub et al, 2006). PAR2 expression in EAO models is upregulated and associated with granuloma formation.…”
Section: Cellular Mechanisms Of Testicular Immune Privilegementioning
confidence: 99%
“…Tryptase activates PAR 2 on keratinocytes [47], endothelial cells [48], testicular peritubular cells [49], and other types of cells (reviewed in [50]). Tryptase is a less potent activator of PAR 2 than trypsin, and the ability of tryptase to activate PAR 2 dramatically decreases depending on receptor glycosylation at a site close to the activation site [40,41].…”
Section: R) Available Receptor Antagonists or Inhibitorsmentioning
confidence: 99%